2016
DOI: 10.1007/s00226-016-0868-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of formaldehyde emission from plywood using composite resin composed of resorcinol–formaldehyde and urea-modified scallop shell nanoparticles

Abstract: More than 200,000 tons of scallop shells are disposed annually alone in Japan. 1 Nanoparticles derived from scallop shells have the potential to adsorb gaseous 2 formaldehyde; therefore such discarded shells have now been tested as additive filler in 3 plywood adhesive by mixing high specific surface area, urea-modified shell nanoparticles 4 with a resorcinol-formaldehyde resin; with this procedure it was found that the emission of 5 formaldehyde from the resulting plywood could be substantially reduced. The 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, with increasing concern about environmental pollutants produced from the formaldehyde of the U/F resin, researchers have focused on environmentally friendly polymers for reducing the amount of formaldehyde. Lots of effort has been taken to reduce formadehyde emissions by adding compounds into U/F, including core flour [ 23 , 24 ], glycolysis products [ 25 ], scallop shell nanoparticles [ 26 ], nano SiO 2 [ 27 , 28 , 29 ], nanocrystalline cellulose [ 30 ], and corn flour [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing concern about environmental pollutants produced from the formaldehyde of the U/F resin, researchers have focused on environmentally friendly polymers for reducing the amount of formaldehyde. Lots of effort has been taken to reduce formadehyde emissions by adding compounds into U/F, including core flour [ 23 , 24 ], glycolysis products [ 25 ], scallop shell nanoparticles [ 26 ], nano SiO 2 [ 27 , 28 , 29 ], nanocrystalline cellulose [ 30 ], and corn flour [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously we investigated the reduction of the formaldehyde emission from a UF/natural scavenger (scallop shell nanoparticles, main component was calcium carbonate). 51 To reduce the emission, the contained particles should be over 80 wt% of the total weight of the solid content of UF resin and the scavenger ( Table 1 ). Herein a graphite amount of 1.9 wt% or less was insufficient to prevent formaldehyde emission.…”
Section: Resultsmentioning
confidence: 99%
“…There are some interesting reports on using nanomaterials in UF adhesive to reduce formaldehyde release from the final products, that is, MDFs 27–31 . Cademartori et al reported alumina nanoparticles as a novel formaldehyde scavenger for UF resin.…”
Section: Introductionmentioning
confidence: 99%